Identifying Messenger Platform Preferences using Multiple Linear Regression and Conjoint Analyses - Evi Triandini; I Gusti Ngurah Satria Wijaya; Riza Wulandari; Ni Wayan Cahya Ayu Pratami; I Ketut Putu Suniantara; Candra Ahmadi (Universitas Airlangga, 2022)
Background: The rapid development of telecommunication technology has prompted the creation of various messenger applications. The competition among social messengers to gain market share is becoming tighter. Objective: This study aims to capture user preferences for messenger platforms and inform software development companies to improve their products based on user needs. Methods: This research uses quantitative methods, i.e., categorical analysis and multiple linear regression analysis, to extend the results from qualitative methods that identify the preferences in past studies. The data were obtained through a questionnaire. Results: The results show that customers are influenced by accessibility, flexibility, effectiveness and chat history. Meanwhile, users are influenced by responsiveness, user-friendly interface, performance, personal needs, privacy and security, and customer services. Conclusion: The research can identify the indicators to guide the creation of an ideal messenger platform based on customer and user preferences. Keywords: Conjoint, Messenger Platform, Multiple Linear Regression, Preference